Asymmetric Special Allowances: A Strategy to Overcome the Retention Crisis of Religious Teachers in Frontier, Outermost, and Underdeveloped Regions - Mariati Sinurat (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
This policy paper examines the urgency of the crisis in the availability and stability of teaching staff, rooted in the low retention and motivation of religious teachers in the Frontier, Outermost, and Disadvantaged (3T) regions. The fundamental problem faced is the mismatch between the nationally uniform amount of special allowances and the reality of high logistics costs and the extreme Construction Cost Index (IKK) in remote areas. This condition of economic vulnerability triggers a high teacher turnover rate, thus widening the gap in the quality of religious education. The strategic issue analysis in this policy study uses the USG (Urgency, Seriousness, Growth) matrix ranking method to prioritize key issues that urgently require immediate resolution. Furthermore, the formulation and evaluation of alternative interventions are analyzed using the William N. Dunn evaluation criteria approach, which includes parameters of effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Five alternative solutions are examined, ranging from career acceleration schemes, provision of standard facilities, scholarship affirmation, to synchronization of regional allowances. Based on the Dunn evaluation matrix scoring results, static and centralized financial incentive schemes have proven unable to respond to local inflation dynamics, thus requiring proportional regulatory reform. Therefore, this paper recommends the establishment of a Minister of Religious Affairs Regulation (PMA) concerning the Asymmetric Special Allowance Scheme. This policy strategically integrates the Construction Cost Index (IKK) coefficient and the level of geographical difficulty as the main variables determining the nominal amount of compensation received.